The novice researcher and the phenomenological pilgrimage - Mitchell, Claire Elizabeth (European Journal for Qualitative Research in Psychotherapy, 2021)
The journey of a novice researcher can be a long and lonely road, which is populated by many unexpected twists and turns. This paper seeks to draw the parallels between engaging phenomenological research and psychotherapy practice to demystify what for many can seem daunting and alien. I share in this article a few of my personal experiences and reflections about reflexivity and engaging my doctoral phenomenological research process that may assist those who have started their research pilgrimage. Learning the new language of phenomenological philosophy is the start. But it is only when we traverse the bends and immerse ourselves experientially that we really get a sense of what phenomenology really requires. Perhaps, like psychotherapy, a phenomenological attitude is always unfolding work in progress.